1983
DOI: 10.1088/0029-5515/23/12/006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ICRF heating near the second harmonic

Abstract: Analytical and numerical results of physical processes taking place around the second-harmonic resonance surface in ICRF heating are presented. It is shown that (1) symmetry of transmission coefficients follow from Onsager's reciprocity relation of the dielectric tensor, and (2) direct dissipation around the cyclotron harmonic layer is mostly due to the Bernstein branch and depends on k‖, becoming low for low k‖. The latter has the consequence that mode conversion and reflection are sensitively reduced by damp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…In the context of the slab model, with the further approximation £ z = 0, our results for P, 5, and J encompass those obtained by other researchers. 3,4 We now consider a single wave mode propagating in a uniform, thermally isotropic, Maxwellian plasma. In such a situation the x variation of the wave field is given by E 0 exp(/7c L x) where k L is in general a complex solution of the hot-plasma dispersion relation for real frequency co. After transformation to cylindrical velocity-space coordinates (v L ,<f>,v z ), the perturbed distribution functions take thq form Applying this fact to an expansion of P about k Lr , P = P(k Lr ) + ik Li dP/bk Lr , and using Eqs.…”
Section: Kli->0mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the slab model, with the further approximation £ z = 0, our results for P, 5, and J encompass those obtained by other researchers. 3,4 We now consider a single wave mode propagating in a uniform, thermally isotropic, Maxwellian plasma. In such a situation the x variation of the wave field is given by E 0 exp(/7c L x) where k L is in general a complex solution of the hot-plasma dispersion relation for real frequency co. After transformation to cylindrical velocity-space coordinates (v L ,<f>,v z ), the perturbed distribution functions take thq form Applying this fact to an expansion of P about k Lr , P = P(k Lr ) + ik Li dP/bk Lr , and using Eqs.…”
Section: Kli->0mentioning
confidence: 99%
“…1 ' 2 More recently, conservation relations have been presented in conjunction with differential equations which model wave propagation and mode conversion near the second ioncyclotron resonance. 3,4 The formalism we present encompasses the previous work and the precise definition of local power absorption provides a clear extension to other applications such as higher-harmonic or minority-ion heating.…”
mentioning
confidence: 99%
“…A number of codes have been developed and applied to MC studies in 1-D geometry. [27][28][29][30][31][32][33][34] The simulations have shown that the wave reflections and cavity effects are of primary importance for the MC process. These phenomena can manifest themselves as a sharp increase of the antenna radiation resistance 35 and of the power absorbed in MC layer vicinity.…”
Section: Status Of the Problemmentioning
confidence: 99%
“…The energy conserving equations have been derived by several researchers [16][17][18][19] for the second harmonic problem using a finite Larmor radius expansion, which is not valid for the present case. It has been reported that both numerical results often agree within the limits of numerical accuracy, 20 although there is a significant difference in the conversion coefficient in particular in some cases.…”
mentioning
confidence: 96%